A New Less Invasive Technique for Multiple-Level Spontaneous Spinal Epidural Hematomas: Wash-and-Go Technique - Tanriverdi, Osman; Gungor, Abuzer; Coban, Mustafa Kemal; Okay, Onder; Kamaci, Umit (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2017)
Aim Spinal epidural hematomas are rare entity in neurosurgery practice. Most of them are spontaneous due to anticoagulant therapy and called spontaneous spinal epidural hematomas (SSEHs). Laminectomy or hemilaminectomy for affected levels is still the first choice in the operative treatment of an SSEH. We describe a new less invasive surgical technique, performing single-level laminectomy and washing with 0.9% sodium chloride through a thin soft catheter for a 12-level thoracic-cervical SSEH in a patient under anticoagulant therapy.Patient and Operative Technique A 55-year-old woman was brought to the emergency department with a rapid onset of pain in her upper back and both legs with weakness of her lower extremities. An urgent magnetic resonance imaging (MRI) of the whole spine showed a SEH. During the operation, after T2 laminectomy, a thin soft catheter was epidurally placed under the T1 lamina and gently pushed forward rostrally. Then continuous saline irrigation was utilized and aspiration made via the catheter to wash out the hematoma. Drainage of blood was observed. The procedure was performed for 15 minutes. Then the catheter was epidurally placed under the T3 lamina, and the procedure for the hematoma in the lower segment was repeated. Decompression of spinal cord and nerve roots was observed.Result Postoperative early MRI of the thoracic-cervical spine showed gross total evacuation of the SEH. Accordingly, the patient's muscle strength improved.Conclusion Although multiple laminectomy or hemilaminectomy for affected levels to evacuate the hematoma and decompress the spinal cord is the main choice of surgical treatment, single-level laminectomy and irrigation plus aspiration via a thin soft catheter can be performed successfully with good results in SSEH.
Keywords: spinal; epidural hematoma; washing out; multilevel